Analisis Kemampuan Berfikir Kritis Matematis Siswa Dalam Pemecahan Masalah Matematika Pada Materi Bangun Datar Kelas Vii Semester Genap - Hafiyyan, Zayan; , Prof.Dr.Budi Murtiyasa,M.Kom (2017)
ABSTRACT This study aims to describe students' mathematical critical thinking skills in solving mathematical problems in the matter of flat wake of class VII even semester. Critical thinking ability in problem solving there are 4 indicators. These four indicators provide simple explanations and build basic skills in understanding problems, organize strategies and tactics to solve problems in making problem-solving plans, provide further explanation in implementing problem-solving plans and conclude in re-checking of what has been done. The type of this research is qualitative research. The subjects of this study were two students taken from class VII B in SMP N 1 Sambi academic year 2016/2017. Data collection techniques used in this study are test techniques, documentation techniques and interview techniques. The validity of data using triangulation techniques and triangulation of sources, while data analysis techniques using data reduction, data presentation and conclusion. The lowest percentage gain of 12.98% means that some students during the execution conclude and re-check what has been done. The highest percentage of 33.77% means that the students during the work have been able to set the strategies and tactics to solve the problem in making problem-solving plans. The results of this study indicate that terdpat 4 ability that must be met students to have critical thinking skills in problem solving. Keywords: Ability, Critical Thinking, Problem Solving, Plane